El diccionario léxico digital para la práctica de la lectura y escritura en los estudiantes de bachillerato de la Unidad Educativa “Carlos Cisneros”, Riobamba, período académico 2021-2022 - Bravo Andrade, María Belén (2023)
Dictionaries constitute a teaching-learning resource for any curricular area, since among their advantages, they highlight competence in linguistic communication, the competence to learn, autonomous work, among others. The objective of this study was to determine the functionality of the digital lexical dictionary in the practice of reading and writing in high school students from “Carlos Cisneros” Educational Unit for the period 2021-2022. This research was carried out using a non-experimental design, in which an intentional and non-probabilistic sample of the population was considered, which corresponded to 183 students from 1st, 2nd and 3rd year of baccalaureate who were surveyed and in the same way, an interview was carried out with the teachers in order to find out their opinion in the context of the use of dictionaries. Among the results, it was found that students use dictionaries very rarely and only for specific activities carried out in the classroom. In addition, students have the technological resources to search for digital or lexical dictionaries, however, they are unaware of their usefulness, while the usefulness of this is sometimes to search for the meaning of a word. In the same way, teachers consider the use of dictionaries in class to be very important, as a strengthening mechanism for the learning process. For these reasons, the use of dictionaries must be redirected to develop reading and writing practice in a timely manner, also considering teaching support, which is essential for the understanding of definitions and linguistic communication.